The Effect Of Ralistic Mathematics Learning Model And Project-Based Learning Model On Problem Solving Ability And Motivation Of Students In Class V Private Sd Markus Medan Helvetia - D. Yuliana Sinaga (CV. Inara, 2022)
This study aims to determine: (1) the difference in the average increase in problem solving skills between students who are taught with a realistic mathematics approach and project-based learning ; (2) the difference in the average increase in student motivation between students taught with a realistic mathematics approach and project-based learning ; (3) improving students' problem-solving skills between those taught with realistic mathematics approaches and project-based learning ; (4) increase in student motivation among students who are taught with a realistic mathematics approach and project-based learning . The research is in the form of a Pre Experimental Design with a Two Group Pretest-Posttest research design . The instruments in this research are problem solving ability test and student motivation questionnaire . The data analysis uses t-test and gain scores. The results of the study show: (1) there are differences in problem-solving abilities, students who are taught by project-based learning are better than those with a realistic mathematics approach , this is based on the t - count value (= 0.001 ) so that there is a difference because sig (2-tailed) < 0.05 and t count is positive ; (2) there is a difference in student motivation taught by project-based learning is better than with a realistic mathematics approach , this is based on the value of t count (= 0.001 ) so there is a difference because sig (2-tailed) < 0.05 and t count is positive ; (3) The improvement of the problem solving ability of students who are taught by project-based learning is higher than the realistic mathematics approach , this is based on the gain score; (4) the increase in student motivation taught by project-based learning is higher than the realistic mathematics approach , this is based on the gain score.